Development of a Nanotechnology E-Module Based on Problem Based Learning Using the Heyzine Application for the Independent Curriculum - Arizona; Syamsi Aini (Jurnal Penelitian Pendidikan IPA, 2025)
Chemistry learning is still considered a difficult learning process, because it focuses on collecting facts and concepts and does not implement an independent curriculum that emphasizes concept discovery. This study aims to produce a nanotechnology-based problem-solving e-module using the Heyzine application for Independent Curriculum, analyze the validity and practicality of the E-module and analyze the effectiveness of the E-module. The type of research used is Research and Development (R&D) with a 4-D development model. The 4-D development model consists of 4 stages of development, namely define, design, develop and disseminate. The validity test uses the Aiken's V formula. The results of the validity test for the content component and presentation component are 0.91 and 0.90 respectively with a valid category. The results of the module practicality test carried out by teachers and students are 0.97 and 0.90 respectively with a very practical category. The effectiveness test of the E-module was carried out using the N-Gain test and obtained a result of 0.77 with a high category. The results of the study indicate that a valid, practical and effective problem-based nanotechnology E-module has been obtained.